Mixed methods research on the role of pupils as assessors in quality assurance of schools in Malta. (January 2018) - Pulis, Angele
This article describes a study conducted in Malta on pupil voice in the role of assessor. The purpose of the study was to provide a fresh perspective on school quality assurance in Malta, by asking those who are directly affected – the pupils themselves. The data provided by the study could help educational leaders, together with the whole school community to understand how schools in Malta are perceived and judged by pupils. The results could provide valuable knowledge for more effective and more efficient appraisal of schools. Ultimately, the findings could shed light on proposals for better-quality schools in Malta. The main research question of the study was: From the pupils' perspective, what are the quality indicators of a good school? The article describes how, and why, the study adopted a mixed methods approach, gathering both quantitative and qualitative data to address the research questions in a way that allowed multiple perspectives to be considered. The main research instrument was a questionnaire survey, collecting largely quantitative data, in which 1618 pupils participated. This was complemented by qualitative data collected through focus group sessions with pupils, group interviews with student councils and one-to-one interviews with heads of schools and policymakers. Data was gathered from a total of 42 different schools.